Motivation to learn Czech as L4+: Erasmus students' perspective - Převrátilová, Silvie (Foreign language annals, 2024)
The Challenge Motivation in language learning is an extensively discussed topic, but little has been said about learning a small language and the primary sources of motivation to learn it as L4+. How is learning Czech different from learning a large world language? What are the classroom implications? Although motivation is an extensively discussed topic, minor languages deserve more research attention. This qualitative multiple case study explores motivation to learn Czech as a second language in Beginners' Czech language courses for Erasmus students in the Czech Republic through the lens of the L2 Motivational Self System (L2MSS), searching for the critical motivation sources in this type of setting. The data were collected in language learning journals, two semistructured interviews, and a final questionnaire. Five cases were chosen to demonstrate the key sources of motivation. In the profiles, the ideal L2 self, closely tied to the sojourn in the country, and the L2 learning experience in the language course were the most prominent components of the L2MSS. The data also suggested a possible role of the multilingual self. Finally, the paper presents pedagogical implications suitable for this type of course and broader instructional contexts.